Homosexualiteit - Overing, A.F.C.; Kempe, G.Th.; Vermeulen, Jos; Trimbos, C.J.B.J. (Hilversum-Antwerpen: Paul Brand, 1964)
"redactie Mr. L. C. Baas, Paul Brand jr., Mgr. Mr. A. A. W. Diepenbrock ... et al. Fonds Suzan Daniel (FSD)"